Gammu and kalkun for information services and sales based on information technology - Joseph Teguh Santoso; Mars Caroline Wibowo; Budi Raharjo; Mufadhol Mufadhol (Institute of Advanced Engineering and Science, 2020)
The rapid development of information technology forces everything to be done sophisticated, easy, and practical. During the information technology revolution 4.0 which is commonly called the disruptive era, the people need communication to exchange information and data. One of the communication systems that has been found today is handphone technology that can be used to communicate remotely through short message services. It can be ascertained that almost every adult having a handphone can be even more than one number, so it is a top priority for market sharing in business activities by utilizing gammu and kalkun technology. Gammu which is an open source program application was developed to build SMS gateways and or while the kalkun program application is used for web based SMS management system. This paper describes the use of gammu and kalkun in information technology to develop and manufacture and manage SMS SERVER effectively and certainly can save costs. This method is more efficient because it allows companies to easily manage their own information dissemination and sales activities and according transactions to business needs, so that the budget spent by the company can be reduced and more economical.